Kebermaknaan Hidup Dan Kecemasan Terhadap Kematian Pada Pasien Kanker - Robertus Surjoseto; Devy Sofyanty (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Someone’s level of death anxiety might elevated if that person is experiencing health problem or chronic disease such as cancer. This study aims to determine the relationshop between those two variables that is the meaning of life and death anxiety in cancer patients. This study used the quantitative method, the sampling technique used was purposive sampling, research subjects are patients with a cancer diagnosis and still undergoing treatment or recovery treatment in the dr Cipto Mangunkusumo Hospital Jakarta, the number of subject obtained was 65 patients. The data was collected using the meaning of life scale (15 aitem, α = 0,854) and death anxiety scale (20 aitem, α = 0,871). The data obtained were analyzed using Person Product Moment.Results of the analysis shows that there is a significant negative relationship between the meaning of life and death anxiety in cancer patients at dr Cipto Mangunkusumo Hospital Jakarta.Negative relationship between the two variable means that the higher the meaning of life , the death anxiety will be lower. Based on the results of this study, there is a need for strategies for cancer patients to increase the meaning of life as an effort to achieve positive adaptation to death anxiety.